Cumulative Rehearsal and Auditory Verbal Memory of Persons with Down Syndrome - Dada, Oluseyi Akintunde; Okpara, Anulika Chinyere; Adeleke, Owoade Philip; Okon, Maureen Okang; Merimekwu, Anne; Anagbogbu, Effa German; Petters, Janet; Edu, Grace Onya; Eno, Asuquo; Akah, Levi Udochukwu; Olufu, Martin Afen (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
One of the characteristics of persons with Down syndrome is poor memory, especially the Auditory-Verbal Memory (AVM). Lack of verbal memory among persons with Down syndrome is one major factor that inhibits learning. This is why the effort towards enhancing AVM of persons with Down syndrome is evolving. This study, therefore, investigated the efficacy of cumulative rehearsal on auditory verbal memory of persons with Down syndrome with speech production and gender as moderator variables. A 2 x 2 x 2 factorial matrix of pretest-posttest control group experimental design was used in the study. A sample of thirty participants was drawn from a population of 44 persons with Down syndrome and randomly assigned to control and experimental groups in two special schools; National Orthopaedic Special School, Igbobi, and Modupe Cole Memorial Childcare and Treatment Home/School, Akoka. Data was collected using a validated self-developed instrument, Auditory Verbal Memory Assessment Scale (AVMAS) (r-0.86). Two hypotheses were tested using ANCOVA. Findings from the study revealed that: cumulative rehearsal therapy significantly impacted the auditory-verbal memory of persons with Down syndrome, with significant improvement observed. There was no significant interaction effect of speech level and gender with the therapy. It was thus concluded that cumulative rehearsal therapy is effective in enhancing auditory-verbal memory and so recommended for the improvement of AVM of persons with Down syndrome.